ASSOCIATION OF AGE, BLOOD PRESSURE, AND BODY MASS INDEX WITH TOTAL CHOLESTEROL LEVELS AMONG MINING WORKERS - Sumardiyono Sumardiyono (Kesmas Indonesia, 2026)
The purpose of the study was to determine the relation between age, body mass index (BMI), and blood pressure and total cholesterol levels in mining workers in PT Harmoni Panca Utama, Job Site KDA. The cross-sectional design was used and a multiple linear regression was carried out to determine the relationship between the independent variables and the overall cholesterol levels. The analysis showed that age and BMI were significant in influencing the level of total cholesterol (p < 0.001), but the systolic and diastolic blood pressure did not exhibit significant relations. Age was associated with more LDL and total cholesterol deposition because of age-related changes in lipid metabolism, and the excessive body weight (BMI) was associated with dyslipidemia because of visceral fat deposition and dysfunctional lipoprotein metabolism. These results have highlighted the significance of occupational health-serial of monitoring concerning the age and the nutritional status of workers to avoid cardiometabolism complications.